FORMULASI SUSPENSI DOKSISIKLIN MENGGUNAKAN SUSPENDING AGENT PULVIS GUMMI ARABICI: UJI STABILITAS FISIK DAN DAYA ANTIBAKTERI - Chasanah, Nur; Trisharyanti DK, Ika; Indrayudha, Peni (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2011)
Suspension is a dosage contain solid drug material with insoluble form and smooth. Doxycycline is an antibiotic which difficult dissolve in water. Stable doxycycline suspension during 2 week if it kept at space temperature, stable on the air but will change to be dark if it influence sunshine. The aim of the research to evaluate physical stability and ability antibacterial stability doxycycline suspension with PGA as suspending agent. Research category are: Independent variable : concentration of suspending agent (PGA), suspension holding time. Dependent variable: physical stability (sedimentation volume, viscosity, redispersibility, easy to pour, and particle size) and antibacterial of doxycycline suspension, and variabel control is temperature suspension making, create of suspension. Data collecting with measuring physical stability and ability antibacterial of doxycycline suspension. The result shows doxycycline suspension with suspending agent PGA had physical stability and antibacterial ability is good. Physical Stability test showÂ  formula 1 rate PGA 5% is formula had physical stability better than formula 2 with rate PGA 7,5% and formula 3 withrate PGA 10%. stability ability test antibacterial show formula 2 is theÂ  best in pursues Staphylococcus aureus.